A responsabilidade civil dos hospitais privados - Cavalcante, Christiane (2007)
In recent years, under the liability, grew too much in the number of indemnities demands against private hospitals, especially under the allegation of medical mistakes. The doctor makes mistakes because he is human and makes mistakes because he had a poor training, because it is lacking residence for all graduated from schools of medicine, because he works too and has no time for study and research. Whatever the cause, the fact is that their conduct affects directly the entities hospital because the medical services provided by hospitals derive from the performance of professional doctor, which is the only authorized to practice of medical act. Though there is a close relationship between the hospital and medical liability and it is treated differently between the doctrine and jurisprudence, for the first, in the field of liability and subjective, for the second, objective. It is not the objective responsibility out of the hospitals, but only when acting as simple hospital service providers; outside that event, the hospital responds by attesting that the doctor acted with fault, as well as its own doctor. The proposal of this work is reflecting on the responsibility of private hospitals, particularly on the nature and various forms. In rich, the issue goes beyond the material aspect, so goes through some procedural peculiarities, which directly influences the indemnities demands such as evidences and third-party complaint